Raw material mixing device for glass welding ring processing - CUI WEICHENG (2019)
The utility model discloses a raw material mixing device for processing a glass welding ring. Including a base, wherein two brackets are fixedly mounted at the top end of the base; a cylinder fixing plate is arranged at the top of the bracket; cylinders are mounted at the top ends of the cylinder fixing plates; the output end of the cylinder is connected with a straight plate; a motor fixing seatis fixedly mounted at the bottom end of the straight plate; a motor is arranged at the bottom end of the motor fixing seat; a stirring barrel supporting plate is fixedly mounted in the middle of the bracket; a stirring barrel is arranged at the top of the stirring barrel supporting plate; a top cover is clamped at the top end of the stirring barrel; a rotating shaft clamping seat is arranged in the middle of the top of the top cover; a rotating shaft is movably mounted in the rotating shaft clamping seat; according to the automatic cleaning device, material collection is convenient and fast, the automatic cleaning fun